2013
DOI: 10.1007/s10910-013-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Seven competing ways to recover the Michaelis–Menten equation reveal the alternative approaches to steady state modeling

Abstract: The Michaelis-Menten enzymatic reaction is sufficient to perceive many subtleties of network modeling, including the concentration and time scales separations, the formal equivalence between bulk phase and single-molecule approaches, or the relationships between single-cycle transient probabilities and steady state rates. Seven methods proposed by different authors and yielding the same famous Michaelis-Menten equation, are selected here to illustrate the kinetic and probabilistic use of rate constants and to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…We use a strategy similar to the probabilistic singlemolecular approach by King and Altman tackling the Michaelis-Menten enzymatic reaction 77 . Evaluation of the average time to reach the final state of nucleation, made up of an infinite number of paths with varied times of repeated micellation and dissociation processes, gives the effective nucleation rate constant in one twostep mechanism path, k 2 is expressed as follows (see Appendix C for derivation):…”
Section: Conversion Of Micellesmentioning
confidence: 99%
“…We use a strategy similar to the probabilistic singlemolecular approach by King and Altman tackling the Michaelis-Menten enzymatic reaction 77 . Evaluation of the average time to reach the final state of nucleation, made up of an infinite number of paths with varied times of repeated micellation and dissociation processes, gives the effective nucleation rate constant in one twostep mechanism path, k 2 is expressed as follows (see Appendix C for derivation):…”
Section: Conversion Of Micellesmentioning
confidence: 99%
“…The general equations ( 3) and ( 4) from which the mean times of arrival T have been deduced in this article, have been demonstrated in (Michel and Ruelle, 2013). They are of course simpler in the homogeneous case for which all forward and backward rates are equal, u i = u and d i = d. The standard deviation related to the first and second moments are derived below in this simplified case.…”
Section: B Mean Completion Times and Standard Deviations In The Homog...mentioning
confidence: 91%
“…The shortest is this time, the most probable is the transformation of the substrate into a product. We have shown in [9] that T obeys the very general formula…”
Section: Substrate Selectionmentioning
confidence: 99%
“…At the very microscopic level, the most realistic mode of nucleation is a random walk with many micro-steps (say h) including single noncovalent bond additions. We showed that the general formula for the time of first arrival to the end of a chain with h consecutive events is [33]…”
Section: Kinetic Vs Equilibrium Point Of Viewsmentioning
confidence: 99%